Numerical modeling of small impacts on Mars - Rajšić, Andrea (Curtin University, 2021)
The NASA InSight mission placed a seismometer on the surface of Mars in 2019. Since then, several hundred seismic signatures have been recorded. I am collaborating with the NASA InSight science team dedicated to understanding small meteorite impacts occurring on Mars. Such small impacts majorly form in the uppermost crust of Mars, which has focused my thesis research on understanding the properties of the uppermost crust of Mars and connecting these with impact-induced seismic properties.